Age, Hypertension, and Physical Inactivity as Dominant Risk Factors for Stroke: A Population-Based Study in Yogyakarta, Indonesia - Muhammad Abdi Riyantono; Ajeng Tias Endarti; Sumiati Bedah; Telly Purnamasari (Universitas Malahayati, 2026)
ABSTRACT Stroke remains a major public health challenge globally, with a growing burden in low and middle-income countries. Indonesia reports a high prevalence of stroke, particularly in the Special Region of Yogyakarta. However, population-based evidence on dominant individual-level risk factors remains limited. This study aims to analyze stroke risk factors in Yogyakarta based on data from the 2023 Indonesian Health Survey. This population-based cross-sectional study used secondary data from the 2023 Indonesian Health Survey. A total of 8,126 respondents aged ≥15 years residing in Yogyakarta Province were included. The outcome was a self-reported history of physician-diagnosed stroke. Independent variables included age, sex, hypertension, physical activity, diabetes mellitus, coronary heart disease, smoking status, and obesity. Multivariable logistic regression was performed to identify dominant risk factors for stroke. The prevalence of stroke was 0.7% (7 per 1,000 population). After adjustment for potential confounders, older age was strongly associated with stroke (adjusted odds ratio [AOR] = 15.35 for ≥65 years; AOR = 15.80 for 46–64 years). Hypertension was the most influential modifiable risk factor (AOR = 13.69; 95% CI: 6.63–28.25). Low physical activity significantly increased stroke risk (AOR = 3.71 for mild activity and 3.42 for moderate activity). Female sex was independently associated with a lower likelihood of stroke (AOR = 0.33; 95% CI: 0.17–0.63). Stroke risk in Yogyakarta Province is primarily driven by ageing, hypertension, and physical inactivity. Strengthening hypertension control and promoting physical activity, particularly from midlife onward, should be prioritized in primary healthcare and community-based prevention strategies. Keywords: Hypertension, Indonesian Health Survey, Physical Inactivity, Stroke.